Quality Education for the World We Want - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, emphasized that children learned better when we level the playing field at an early stage. He stressed the need for stronger basic education with immediate investment, and a focus on recruitment, grooming, and motivation of teachers. He concluded that we must sustain this momentum and use all available resources and evidence to make sure that every child is in school and learning.